LEFT VENTRICULAR DIASTOLIC DYSFUNCTION AND OXYGEN SUPPLY OF LOWER EXTREMITIES IN PATIENTS WITH STABLE ISCHEMIC HEART DISEASE AND CONCOMITANT TYPE 2 DIABETES MELLITUS - Yarema, N. I.; Pasyechko, N. V.; Khomitska, A. I.; Savchenko, I. P.; Smachylo, I. V.; Naumova, L. V.; Radetska, L. V.; Bob, A. O.; Havrylyuk, M. E.; Bob, O. O.; et al. (International Journal of Medicine and Medical Research, 2017)
Background. The peculiarities of diastolic heart failure and indices of arterial and venous blood oxygenation in patients with stable ischemic heart disease and concomitant type 2 diabetes mellitus are presented in the article. Obvious left ventricular diastolic dysfunction with the increased levels of natriuretic peptide, uric acid and decreased indices of arterial and venous blood oxygenation in the presence of comorbid type 2 diabetes mellitus have been revealed. Objective. The research was aimed to study the peculiarities of left ventricular diastolic function disorders, levels of NT-proBNP, uric acid and indices of arterial and venous blood oxygenation in patients suffering from stable exertional angina with underlying comorbid type 2 diabetes mellitus. Methods. 70 patients with IHD: stable exertional angina of the ІІІ functional class, were examined. The first group comprised 39 patients with stable exertional angina of the ІІІ functional class with left ventricular diastolic dysfunction; the second group – 31 patients with stable exertional angina of the ІІІ functional class with left ventricular diastolic dysfunction and concomitant type 2 diabetes mellitus. All the examined patients underwent BD- echocardioscopy, with the detailed evaluation of left ventricular diastolic function, NT-proBNP and uric acid levels in venous blood were determined by immunoenzyme method, indices of arterial and venous blood oxygenation were evaluated too. Results. The correlation between left ventricle diastolic function and oxygen volume consumed by the tissues of lower extremities in patients with stable ischemic heart disease and concomitant type 2 diabetes mellitus was determined. Conclusions. In patients with stable IHD, left ventricular diastolic dysfunction and concomitant type 2 diabetes mellitus the levels of NT-proBNP, uric acid and oxygen supply of lower extremities are significantly higher as compared to patients with IHD without type 2 diabetes mellitus.